A COMPARATIVE ANALYSIS OF SHARIA-BASED DIRECT SELLING PRACTICES IN MULTI-LEVEL MARKETING: EVIDENCE FROM K-LINK AND HNI BRANCHES IN MATARAM - Muhammad Haeri Iqbal; Haris Cahyadi; Zainuddin Mansyur; Baiq Ratna Mulihmmah (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri Palembang, 2026)
This study analyzes the implementation and comparative practices of Sharia-Based Direct Selling (PLBS) at PT K-Link and PT HNI Mataram Branch, in response to public concerns regarding the compliance of multi-level marketing (MLM) practices with sharia principles, particularly regarding clarity of contracts, bonus mechanisms, transparency, and the avoidance of gharar, maysir, and riba elements. This study uses a qualitative approach with a comparative case study design. Data collection was conducted through in-depth interviews, participant observation, and documentation studies involving branch managers and business partners. Data analysis was carried out through stages of reduction, presentation, and verification with reference to the dimensions of sharia compliance, contract mechanisms, and sharia business ethics. The results show that both companies have formally adopted the main principles of PLBS, including the use of wak?lah bil ujrah contracts, a real sales-based bonus system, halal-certified products, and supervision by the Sharia Supervisory Board. However, there are differences in the depth of implementation, with PT HNI emphasizing sharia guidance and education, while PT K-Link prioritizes system standardization and compensation control. This study confirms that PLBS implementation remains procedural and heavily dependent on internal company interpretations, necessitating clearer theoretical benchmarks and ongoing external evaluation. This research contributes to the development of Sharia-based MLM studies through a more critical, comparative perspective.